A Comprehensive Review of Research on Academic Perspectives Regarding Boko-Haram Insurgency in Northern Nigeria - Nasidi, Nadir Abdulhadi (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2024)
Although scholars have written extensively on different aspects of Boko-Haram insurgency in Northern Nigeria, a systematic review of the literature appears to be lacking. The significance of this study lies in its unique approach to addressing the gap in the literature on the Boko-Haram insurgency in Northern Nigeria. While previous works have explored various dimensions of the insurgency, this study makes an original contribution by conducting a systematic review to synthesize the findings of existing studies published between 2015 and 2023. Scopus and Science Direct databases were searched, and 107 journal articles and book chapters were sampled, out of which 46 were excluded for reasons. While 65 full-text articles were assessed for eligibility, 28 more papers were excluded for not being relevant. 37 studies were selected having met the review criteria. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, this paper shows how scholars approached the phenomenon of Boko-Haram insurgency. Results show that there is a higher number of works on Boko-Haram, accounting for 24.3% and 18.9% of the publications in 2020 and 2023 respectively.